A critical discourse analysis of the language of persuasion used in the election campaigns by American parliaments - Janam, Iman Jabr (al-Ustādh, 2019)
Persuasion can be defined as a scientific art which is closely connected with our life .Linguistically speaking, persuasion is achieved through many techniques termed "persuasive devices". These persuasive devices are covered in different domains of life. Accordingly, persuasion has been defined in various methods according to communication as ''a communication process in which a communicator searches to draw out a desired response from his receiver''. This paper investigates different strategies of persuasion used by different people in different domains of life and how those strategies differ when used in election parliament. The aim of this paper is to find out the strategies of persuasion used by different people and specifically in the election Campaigns. It is hypothesized that Americans use different strategies of persuasion in order to affect others by changing their beliefs, attitudes and so on. This paper explains what is meant by the term "critical discourse analysis", (henceforth CDA), elaborates on the political discourse analysis and shows how it differs from (CDA).Outlining persuasion with its strategies which are used to influence on the others. Besides, it analyzes the data selected for this study which is the speeches of Hillary Clinton and Donald trump through the polling, then discusses the results and conclusions.